Karl Marx’s and Fyodor M. Dostoevsky’s Conception of Socialism - Morillas, Jordi (Hybris, 2018)
In order to provide the necessary background for the discussion on Marx’s and Dostoevsky’s conception of socialism we delineate a brief history of the French Revolution. Then, we analyze the social conditions of the proletariat and how socialism is defined for both thinkers as a mainly economic doctrine. Later, socialism’s theological question is discussed. We point out how Marx and Dostoevsky defend the thesis that religion is socialism’s first target. To that end, we refer to the Marxist concepts of “alienation” and “emancipation” and Dostoevsky’s predicted union of Catholicism with socialist ideals as it is exemplified in The Great Inquisitor. Finally, Marx’s and Dostoevsky’s conception of man is explained, showing how the materialistic interpretation of the human being realized by Marx is radically rejected by Dostoevsky. Likewise, it is exposed the scientific and violent nature of socialism. As a conclusion, we summarize the main similarities and differences between Marx and Dostoevsky and we treat the question about their prophetic character in relation to the socialist movement in Russia, and particularly to the Russian Revolution of 1917.